Pulmonary Metastasis Originated from Uterine Sarcoma, Presenting as Multiple Nodules with Tortuous, Serpentine, Aneurysmal, Dilated Intratumoral Vessels: A Case Report - Hyeon Ji Jang; Song Soo Kim; Hee Sun Park; Jeong Eun Lee; Jin Hwan Kim (대한영상의학회지, 2018)
Pulmonary metastases present a wide spectrum of radiological findings, some of which have been known to be useful for analogizing the possible origin or site of primary tumors. In the present report, we describe a unique case of pulmonary metastasis manifesting on chest computed tomography as multiple nodules with tortuous, serpentine, aneurysmal, dilated, inner intratumoral vessels. The metastasis originated from uterine sarcoma.